2007
DOI: 10.1128/jb.00385-07
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Sinorhizobium meliloti Acetate Metabolism Genes aceA , SMc00767, and glcB

Abstract: The genes encoding malate synthase (glcB) and isocitrate lyase (aceA) and a 240-bp open reading frame (SMc00767) located downstream of aceA were isolated and functionally characterized in Sinorhizobium meliloti. Independent and double interposon mutants of each gene were constructed, and the corresponding phenotypes were analyzed. aceA mutants failed to grow on acetate, and mutants deficient in SMc00767 were also affected in acetate utilization. In contrast, mutants deficient in glcB grew on acetate similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Moreover, the coincident expressions of glyoxylate cycle genes and a subset of nif genes in the chemoautotrophic culture of B. japonicum [84] imply potential coordination in transcriptions of these genes. However, S. meliloti mutants of two principle genes, aceA (encoding isocitrate lyase) and glcB (encoding malate synthase), in the glyoxylate cycle were not impaired in nodulation and nitrogen fixation on alfalfa [85]. NGR_c03920- NGR_c03950 expressed higher in V. unguiculata bacteroids (RPKM = 254–401) than in L. leucocephala bacteroids (RPKM = 55–105) and the free-living condition (RPKM = 24–40).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the coincident expressions of glyoxylate cycle genes and a subset of nif genes in the chemoautotrophic culture of B. japonicum [84] imply potential coordination in transcriptions of these genes. However, S. meliloti mutants of two principle genes, aceA (encoding isocitrate lyase) and glcB (encoding malate synthase), in the glyoxylate cycle were not impaired in nodulation and nitrogen fixation on alfalfa [85]. NGR_c03920- NGR_c03950 expressed higher in V. unguiculata bacteroids (RPKM = 254–401) than in L. leucocephala bacteroids (RPKM = 55–105) and the free-living condition (RPKM = 24–40).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the role of ICL, null mutants were constructed in S. meliloti and Rhizobium tropici and their symbiotic performance was evaluated on M. sativa and Phaseolus vulgaris, respectively. The results demonstrated that in both symbiotic models ICL is not involved in nodulation or nitrogen fixation (Ramírez-Trujillo et al, 2007).…”
Section: Roles Of Icl and Ms In Other Plant-bacteria Interactionsmentioning
confidence: 88%
“…GenArise carries out a number of transformations: background correction, lowest normalization, intensity filter, replicate analysis, and selection of differentially expressed genes. The goal of GenArise is to identify good evidence that the genes are differentially expressed, and it has been successfully used in recent studies (Méndez‐Ortiz et al,2006; Luna‐Moreno et al,2007; Ramirez‐Trujillo et al,2007). The software identifies differentially expressed genes by calculating an intensity‐dependent z‐score.…”
Section: Methodsmentioning
confidence: 99%